2013
DOI: 10.1007/s00210-012-0829-9
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of the vasorelaxing effects of CORM-3, a water-soluble carbon monoxide-releasing molecule: interactions with eNOS

Abstract: The purpose of the present work was to elucidate the mechanisms underlying the endothelium-dependent and endothelium-independent components of the vascular relaxation induced by a water-soluble and ruthenium-based carbon monoxide (CO)-releasing agent, tricarbonylchloro(glycinato)ruthenium(II) (CORM-3). Changes in isometric tension and cyclic guanosine monophosphate (cGMP) production were measured in isolated aortic rings from normotensive Wistar-Kyoto rats. Nitric oxide (NO) generation was assessed in cultured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 47 publications
5
17
0
Order By: Relevance
“…In the present work we clearly demonstrate that CO liberated from CORM‐401 induces NO production in endothelial cells. Similar effects have been described for other CO‐RMs or CO gas in different cell types or vascular tissue preparations . Various mechanisms responsible for NO increase following CO treatment were proposed previously; they include displacement of NO from a cellular storage pool or activation of NO synthase via calcium or phosphatidylinositol 3‐kinase/Akt pathways .…”
Section: Discussionsupporting
confidence: 72%
“…In the present work we clearly demonstrate that CO liberated from CORM‐401 induces NO production in endothelial cells. Similar effects have been described for other CO‐RMs or CO gas in different cell types or vascular tissue preparations . Various mechanisms responsible for NO increase following CO treatment were proposed previously; they include displacement of NO from a cellular storage pool or activation of NO synthase via calcium or phosphatidylinositol 3‐kinase/Akt pathways .…”
Section: Discussionsupporting
confidence: 72%
“…This study is the first to demonstrate a strong vasorelaxant effect of RuCl 3 . Only one study reported a vasoactive effect of RuCl 3 , namely a limited contractile effect on rat aortic rings [17]. This divergence could be due to species differences as already shown for CO and CORM‐2,[12] but this is rather unlikely.…”
Section: Discussionmentioning
confidence: 95%
“…Hence, scavenging of the already low NO levels by ruthenium‐based drugs would seriously counteract their beneficial effect. It was already demonstrated that CORM‐2 attenuates NO donor‐induced relaxations, and that the water‐soluble ruthenium‐based CO‐releasing molecule RuCl(CO) 3 ‐glycinate (=CORM‐3) inhibits endothelium‐ and NO‐dependent relaxations [16,17]. However, the influence of ruthenium itself on NO‐mediated signalling is not completely explored.…”
Section: Introductionmentioning
confidence: 99%
“…This causes a rapid rise in free nitric oxide levels both intracellularly and extracellularly. At the same time, CO has also been shown to be capable of activating certain forms of nitric oxide synthase, resulting in an overall increased production of nitric oxide (Alshehri et al, 2013;Thom et al, 1997b). This dysregulation of NO homeostasis can lead to profound hypotension that is resistant to catecholamines (Fischer and Levin, 2010;Ketteler et al, 1998).…”
Section: Carbon Monoxide and Nitric Oxide Interplaymentioning
confidence: 99%